The role of premorbid and comorbid mental disorders in the pathogenesis and prognosis of PTSD - Коростій, Володимир Іванович; Коровіна, Лідія Дмитрівна (Psychological Counseling and Psychotherapy)
The article discusses the problem of diagnosis of PTSD and comorbid psychiatric disorders. The basic characteristics and comorbidity of PTSD are present. As an illustration, was shown two clinical cases of PTSD with the different variant of comorbidity. In the first case there is a premorbid depressive symptoms in patient with PTSD. In the second case described comorbid schizotypal symptoms. It was shown the relevance of a thorough diagnosis of premorbid and comorbid psychopathology in patients with PTSD for the effective treatment and rehabilitation.